Socioeconomic Status and Hypertension Control in Sub-Saharan Africa: The Multination EIGHT Study (Evaluation of Hypertension in Sub-Saharan Africa). Issue 4 (April 2018) - Antignac, Marie; Diop, Ibrahima Bara; Macquart de Terline, Diane; Kramoh, Kouadio Euloge; Balde, Dadhi M.; Dzudie, Anastase; Ferreira, Beatriz; Houenassi, Martin Dèdonougbo; Hounsou, Dominique; Ikama, Méo Stéphane; Kane, Adama; Kimbally-Kaki, Suzy Gisèle; et al.
Abstract : Systemic hypertension is a rapidly growing epidemic in Africa. The role of socioeconomic status on blood pressure control has not been well studied in this part of the world. We, therefore, aimed to quantify the association of socioeconomic status both at the individual and at the country level with blood pressure control in Sub-Saharan Africa. We conducted a cross-sectional survey in urban clinics of 12 countries, both low income and middle income, in Sub-Saharan Africa. Standardized blood pressure measures were made among the hypertensive patients attending the clinics. Blood pressure control was defined as blood pressure <140/90 mm Hg, and hypertension grades were defined according to the European Society of Cardiology guidelines. A total of 2198 hypertensive patients (58.4±11.8 years; 39.9% men) were included. Uncontrolled hypertension was present in 1692 patients (77.4%), including 1044 (47.7%) with ≥grade 2 hypertension. The proportion of uncontrolled hypertension progressively increased with decreasing level of patient individual wealth, respectively, 72.8%, 79.3%, and 81.8% ( P for trend, <0.01). Stratified analysis shows that these differences of uncontrolled hypertension according to individual wealth index were observed in low-income countries ( P for trend, 0.03) and not in middle-income countries ( P for trend, 0.26). In low-income countries, the odds of uncontrolled hypertension increased 1.37-fold (odds ratio, 1.37 [0.99–1.90]) and 1.88-fold (odds ratio, 1.88 [1.10–3.21]) in patients with middle and low individual wealth as compared with high individual wealth. Similarly, the grade of hypertension increased progressively with decreasing level of individual patient wealth ( P for trend, <0.01). Strategies for hypertension control in Sub-Saharan Africa should especially focus on people in the lowest individual wealth groups who also reside in low-income countries. Abstract : Supplemental Digital Content is available in the text.